The promising role of probiotics/prebiotics/synbiotics in energy metabolism biomarkers in patients with NAFLD: A systematic review and meta-analysis - Li, Shudi; Liu, Jiangkai; Wang, Zhen; Duan, Fei; Jia, Zi; Chen, Xinju; Li, Suling (Frontiers in Public Health, 2022)
Background Nonalcoholic fatty liver disease (NAFLD) is a chronic liver disease with a high prevalence worldwide, seriously harming human health, and its pathogenesis remains unclear. In recent years, increasing evidence has indicated that intestinal microbiota plays an important role in the occurrence and development of NAFLD. The regulation method of probiotics/prebiotics/synbiotics can alter the intestinal microbiota and has been suggested as an option in the treatment of NAFLD. Methods Five databases of PubMed, Embase, the Cochrane Library, clinicaltrails.gov, and China National Knowledge Infrastructure were searched initially, and then the eligible studies were screened. Finally, the data of included studieswere extracted, combined and analyzed Results A total of 29 randomized controlled trials involving 2,110 patients were included in this study. The results showed that using probiotics/prebiotics/synbiotics in the intervention group could reduce the levels of glucose (SMD = −0.23, 95% CI [−0.45, −0.01], P = 0.04), HOMA-IR (SMD = −0.47, 95% CI [−0.63, −0.31], P < 0.00001) and insulin (SMD = −0.46, 95% CI [−0.76, −0.16], P = 0.002) in sugar metabolism; in terms of lipid metabolism, the levels of TC (SMD = −0.62, 95%CI [−0.87, −0.36], P < 0.00001), and LDL-C (SMD = −0.57, 95%CI [−0.85, −0.28], P < 0.00001) were decreased; and the level of ALB was decreased in protein metabolism (SMD = −0.34, 95%CI [−0.61, −0.06], P = 0.02). Conclusions Based on the current evidence, probiotics/prebiotics/synbiotics may improve energy metabolism biomarkers in the NAFLD population, but these effects still need to be confirmed by further research. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/#aboutpage.